1999
DOI: 10.1007/s12043-999-0123-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of photoconductivity in As-Sb-Se glasses

Abstract: Characteristic features of photoconductivity in AsÜSb½ Se Ü and AsÜSb½¼Se ¼ Ü bulk glass systems have been measured and reported. Both a.c and d.c techniques have been employed for the measurements. The temperature dependence of photoconductivity has been analysed in terms of the ABFH model and both systems are found to exhibit type I photoconductivity. Photoconductivity shows a clear change in slope corresponding to the stoichiometric composition in both the systems. The composition dependence of photoconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The relation between ln(τ) and ln(g) shows that the exponent ν lies between 0.54 and 1, which is an indication for a continuous distribution of traps in the energy gap. 26 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The relation between ln(τ) and ln(g) shows that the exponent ν lies between 0.54 and 1, which is an indication for a continuous distribution of traps in the energy gap. 26 …”
Section: Resultsmentioning
confidence: 99%
“…The value of ν at different light intensities lies between 0.5 and 1. A value of ν lying between 0.54 and 1 is an indication for a continuous distribution of traps in the energy gap 6 Temperature dependence of lifetime for TlGaS 2 single crystals.
7 Applied voltage dependence of lifetime for TlGaS 2 single crystals.
8 Light intensity dependence of lifetime for TlGaS 2 single crystals.
9 Light intensity dependence of the PRT for TlGaS 2 single crystals.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The addition of antimony to chalcogenide glasses is generally accompanied by a marked change in their electrical and photoelectrical properties. To this issue a series of works are devoted [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…All these changes are very significant for various applications including medical and pharmaceutical uses, micro-electro-mechanical (MEMS) devices and imaging. Photoconductivity in various materials has been an area of significant interest [7]- [9]. Investigators have reported various aspects of the phenomenon.…”
Section: Introductionmentioning
confidence: 99%